2018
DOI: 10.1007/978-3-319-78692-6_6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Classroom Discussion

Abstract: Past research has shown that students in schools with greater levels of open classroom discussion, have more positive attitudes toward other groups and hold more democratic attitudes. Students do not learn citizenry only by knowledge acquisition; school practices such as classroom discussion foster critical thinking, help students to understand others and reduce closed-mindedness. Students with a higher exposure to classroom discussion were hypothesized to display more tolerant attitudes to other groups and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…At the classroom level, class-average perceptions of a democratic classroom climate were also associated with less negative attitudes toward immigrants at Time 1. These results are generally consistent with previous studies using more narrow and specific indicators of democratic classroom climate (i.e., perceived teacher support and fairness (Miklikowska et al, 2019), open classroom climate for discussion (Carrasco & Torres Irribarra, 2018), or participation in decision making processes (Higdon, 2015). This study therefore replicates the effects found in existing literature with a broader indicator of democratic classroom climate.…”
Section: School Experiences and Attitudes Toward Immigrantssupporting
confidence: 91%
See 1 more Smart Citation
“…At the classroom level, class-average perceptions of a democratic classroom climate were also associated with less negative attitudes toward immigrants at Time 1. These results are generally consistent with previous studies using more narrow and specific indicators of democratic classroom climate (i.e., perceived teacher support and fairness (Miklikowska et al, 2019), open classroom climate for discussion (Carrasco & Torres Irribarra, 2018), or participation in decision making processes (Higdon, 2015). This study therefore replicates the effects found in existing literature with a broader indicator of democratic classroom climate.…”
Section: School Experiences and Attitudes Toward Immigrantssupporting
confidence: 91%
“…There is also empirical evidence that a democratic classroom climate is associated with positive intergroup attitudes (e.g., Solhaug & Osler, 2018). It should be noted, however, that democratic climate covers a broad spectrum of school experiences and, accordingly, has mostly been operationalized through various distinctive facets, such as open classroom climate for discussion (e.g., Carrasco & Torres Irribarra, 2018), fairness of teachers (e.g., Miklikowska et al, 2019), or opportunities for participation in decision making processes (e.g., Higdon, 2015).…”
Section: School and Classroom Climate And Youth's Intergroup Attitudesmentioning
confidence: 99%
“…Class discussion means an interaction between teachers and students with the purpose of developing students' capabilities to expand their understanding (Witherspoon et al, 2016). According to Carrasco and Irribarra's (2018) study, through class discussion, students know how to accept controversial voices and learn from each other. Asking effective questions with clear direction is a good way to lead class discussion because students can grasp the "central idea" that makes the discussion more effective (Dallimore, Hertenstein, & Platt, 2004).…”
Section: English Immersion Programmentioning
confidence: 99%
“…They will express their feeling together and turn to be active and proactive students. Moreover, mutual communication can enhance the motivation of all group members (Carrasco & Torres Irribarra, 2018;Murphy et al, 2009).…”
Section: Cooperationmentioning
confidence: 99%